KIMS modification of Alvarado’s score for acute appendicitis - Premkumar, Daivasikamani (International Surgery Journal, 2017)
Background: Abdominal pain is one of the most frequent presentations to the emergency department (ED). Acute appendicitis is by no means an easy diagnosis to make and can baffle the best. Problems related to the diagnosis of appendicitis are evidenced by the significant negative laparotomy rate. A scoring system described by Alvarado was designed to reduce the negative appendicectomy rate without increasing morbidity and mortality. Alvarado’s score does not include ultrasonogram which is most commonly done investigation before any abdominal surgery. Methods: The study included the ultrasonography and modified the scoring system and retrospectively we analyzed 153 patients who were admitted as acute appendicitis. When interpreted considering the clinical examination, sonography and modified scoring system and it significantly reduced the rate of false-negative appendectomies. The use of diagnostic imaging tests such as CT scan or ultrasonography should be selective in those with atypical presentation or findings. Laparoscopy, barium enema, ultrasonography and computer assistance have all been shown to improve accuracy, but no one method is of proven superiority. Results: By using KIMS modification of Alvarado’s score it was found that unnecessary appendectomy can be avoided in 11 out of 132 patients. Conclusions: Such diagnostic aids or intensive in-hospital observation must be used to reduce the 15-30 per cent negative laparotomy rate when acute appendicitis is suspected, without increasing the incidence of appendiceal perforation.